Recent advances in invasive coronary treatment strategies for out-of-hospital cardiac arrest: are they working?. (August 2015) - Radsel, Peter; Noc, Marko
Chain of survival in out-of-hospital cardiac arrest is improving and more patients are being admitted. Coronary disease is the leading cause of cardiac arrest. Patients return to consciousness after return of spontaneous circulation follow ESC/AHA guidelines on acute coronary syndrome management, but there is debate on how to approach comatose patients. There is consensus that the STEMI subgroup with shockable rhythm should be brought directly to the catheterization laboratory as they have acute coronary lesion in 90% of cases and expected survival of more than 50%. On the other hand, there is a big debate on whether patients without STEMI benefit from an early invasive approach as acute coronary lesion is found less frequently. Nonshockable first rhythm carries a much worse prognosis, and a less invasive strategy in this subgroup seems reasonable.